Html5: the new basic standard of the Web - Franganillo, Jorge (Anuario ThinkEPI, 2011)
In late 2009 the W3C stopped developing xhtml2 and focused on defining html5 instead. Since then, there has been some confusion and heated debates about the proper markup language for future web development. Html5 was conceived with the aim of simplifying the designers´ work and improving the sites´ performance, especially on mobile devices. This paper analyzes the final draft of the html5 specification and discusses the most significant issues: syntax, DOM, information gathering and presentation, and multimedia processing.